Trends and prediction of incidence and mortality burden of larynx cancer in China and the US: a systematic analysis of the Global Burden of Disease Study 2021 - Xu, Weimin; Gan, Hui; Ye, Yuhua (Frontiers in Oncology, 2025)
ObjectivesThis study aimed to compare and predict the disease burden of larynx cancer in China and the United States (US) using data from the Global Burden of Disease Study 2021 (GBD2021).MethodsWe used the data from GBD2021 to systematically analyze and compare the incidence and mortality of laryngeal cancer in China and the United States, and used the Autoregressive Integrated Moving Average (ARIMA) model to predict the trends in the next 10 years.ResultsIn 2021, China had 38,904.86 (95% UI: 30,369.67–49,486.18) larynx cancer cases and 19,799.45 (95% UI: 15,579.57–25,023.24) deaths, reflecting a 2.52-fold and 53.8% increase from 1990. In the US, there were 16,371.45 (95% UI: 15,509.40–17,060.58) cases and 4,620.32 (95% UI: 4,339.97–4,835.98) deaths, showing a 33.3% and 10.04% increase from 1990. Projections indicate a decline in age-standardized incidence and mortality rates in China, while the US is expected to see a slight decline in incidence but continued significant reductions in mortality.ConclusionsChina has a significantly higher number of larynx cancer cases compared to the US, with a higher incidence rate. However, mortality rates are relatively similar. Larynx cancer will remain a notable disease burden in both countries over the next decade.